Structured reporting of CT scans of patients with trauma leads to faster, more detailed diagnoses: An experimental study. Issue 144 (November 2021) - Jorg, Tobias; Heckmann, Julia Caroline; Mildenberger, Philipp; Hahn, Felix; Düber, Christoph; Mildenberger, Peter; Kloeckner, Roman; Jungmann, Florian
Highlights: Structured reporting of CT trauma scans was compared to free-text reporting in an experimental setting. Structured reporting led to faster documentation of diagnoses. Structured radiology reports contained more detailed designations of pathologies. Radiologists were more satisfied with structured reports. Abstract: Purpose: This study aimed to determine whether structured reports (SRs) reduce reporting time and/or increase the level of detail for trauma CT scans compared to free-text reports (FTRs). Method: Eight radiology residents used SRs and FTRs to describe 14 whole-body CT scans of patients with polytrauma in a simulated emergency room setting. Each resident created both a brief report and a detailed report for each case using one of the two formats. We measured the time to complete the detailed reports and established a scoring system to objectively measure report completeness and the level of detail. Scoring sheets divided the CT findings into main and secondary criteria. Finally, the radiological residents completed a questionnaire on their opinions of the SRs and FTRs. Results: The detailed SRs were completed significantly faster than the detailed FTRs (mean 19 min vs. 25 min; p < 0.001). The maximum allowance of 25 min was used for 25% of SRs and 59% of FTRs. For brief reports, the SRs contained more secondary criteria than the FTRs (p = 0.001), but no significant differences were detected in main criteria. Study participants rated their own SRs as significantly more time-efficient, concise, and clearly structured compared to the FTRs. However, SRs and FTRs were rated similarly for quality, accuracy, and completeness. Conclusion: We found that SRs for whole-body trauma CT add clinical value compared to FTRs because SRs reduce reporting time and increase the level of detail for trauma CT scans.